الإمام يوسف تشن كه لي (Chen Keli) ومنهجه في ترجمة وشرح كتاب "التاج الجامع للأصول" للشيخ منصور علي ناصف /‏ - وو، لي هوا (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This research aims to introduce the Imam Yusuf (Cheng KeLi) and the study of his book "Talking Book" in an analytical study. The researcher used the following approaches: historical descriptive approach in order to display historical information concerning the life of the author and his book "Talking Book". The inductive method used to tracking the subject of the message and gather information. The analytical method demonstrates the approach of Imam Yusuf in the translation of the book "Crown". The researcher first exposed the statement by Imam Yusuf about the circumstances of his time, explaining their influence, and his personal life and scientific life, and describes his book and its place among the books that translated Al-hadith, with an indication of the approach taken by the translation and explanation. The most important areas in the book "Talking book" are given together with examples. In conclusion, the researcher mentions the most important findings with some of the recommendations, and the results of the study are summarized in two important points: First, that Imam Yusuf was not only an Imam, he was also a scientist, thinker, Zahid and Shahid. Second: This book is unique, benefitting all sections of jurisprudence. There has never in the history of China's translation a comprehensive book with explanation of the Sunnah, the collection of all Fiqh before this book; that the efforts that preceded it about talking books was take care by the translation of the words chosen talk with a little, and did not explain Al-hadith and shed light on their meanings.